2009
DOI: 10.1109/tap.2008.2009778
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Pyramidal Antenna Loaded With a Cutoff Open-Ended Waveguide

Abstract: An original and flexible pyramidal antenna for satellite or terrestrial application services is presented. The ground plane of the antenna is perforated and loaded with a cutoff open-ended waveguide: this original configuration leads to a good tradeoff between rear radiation and impedance matching. Trap-loads are used to achieve multiband operation while frequency agility may be simply obtained by loading the radiating element by radio-frequency switches. The antenna radiates linearly or circularly polarized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The originally proposed pyramidal antenna consists of 4 inclined radiating elements printed on a square-base pyramid [1], [2]. Trap-loads are used to achieve resonant multifrequency behavior.…”
Section: Multiband Pyramidal Antennamentioning
confidence: 99%
See 3 more Smart Citations
“…The originally proposed pyramidal antenna consists of 4 inclined radiating elements printed on a square-base pyramid [1], [2]. Trap-loads are used to achieve resonant multifrequency behavior.…”
Section: Multiband Pyramidal Antennamentioning
confidence: 99%
“…To improve input matching of the pyramidal antenna, the authors suggested to make a hole in the ground plane and continuing this hole by a cut-off cylindrical waveguide to keep reasonable rear radiation level [1]- [3]. This waveguide is designed such that no modes are propagating inside of it at the operating frequencies of the antenna.…”
Section: Multiband Pyramidal Antennamentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate the requirement of multi‐band communication applications, different antennas have been designed and developed [1–18]. Modified T‐shape radiating structure for multi‐band operation is proposed [1].…”
Section: Introductionmentioning
confidence: 99%